Estimation of Postmortem Interval by Measuring Potassium Level in Vitreous Humour - Bohra, Bhavesh; Verma, Ramakant; Mathur, Indu Bala; Sharma, Yogesh; Khangwal, Vijay Pal; Joshi , Manoj (Journal of Indian Academy of Forensic Medicine, 2015)
Establishing the postmortem interval is one of the difficult challenges faced by forensic experts,  particularly when limited information about deceased is available. Various methods have been tried to find  out the time of death. These include study of physical, chemical, biochemical, histological and enzymatic  changes which occur progressively in dead body. The chemical changes to determine the postmortem  interval have been increased largely in the last few decades, which are based on changes occurring in  the body immediately or shortly after death. These changes occur in various body fluids such as whole  blood, serum, CSF, aqueous and vitreous humour. In this study vitreous humour potassium concentration  were investigated to predict postmortem interval. In this study we have observed linear rise of vitreous  potassium (K+) ion concentration with increasing post-mortem interval that was both arithmatic as well as  logarithmatic (statistically) significant. No significant differences existed for vitreous potassium  concentration in the same pair of eyes at identical post-mortem interval. Factors like age, sex, cause of  death and environmental temperature did not influence the vitreous humour potassium values.
Keywords: Postmortem interval; Vitreous humour; Potassium